Teaching English-medium instruction courses in higher education a guide for non-native speakers - Breeze, Ruth; Guinda, Carmen Sancho 1963- (Bloomsbury, 2021)
1. What is English Medium Instruction and Why Are We Doing It? -- 2. What Does Implementing EMI Mean in Practice? -- 3. Lecturing in English -- 4. Interacting with Students -- 5. Assignments and Assessment -- 6. Teamwork, Networks and Resources -- 7. Taking Your Teaching to the Next Level -- 8. Achieving Excellence in Global Settings -- References -- Index
Keywords: College teachers / Training of; Education, Higher; English language / Study and teaching / Foreign speakers; English-medium instruction; ELT: English for academic purposes